2017
DOI: 10.18632/oncotarget.14988
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and validation of potential urinary biomarkers for bladder cancer diagnosis using a pseudotargeted GC-MS metabolomics method

Abstract: Bladder cancer (BC) is the second most prevalent malignancy in the urinary system and is associated with significant mortality; thus, there is an urgent need for novel noninvasive diagnostic biomarkers. A urinary pseudotargeted method based on gas chromatography–mass spectrometry was developed and validated for a BC metabolomics study. The method exhibited good repeatability, intraday and interday precision, linearity and metabolome coverage. A total of 76 differential metabolites were defined in the discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Gas chromatography mass spectrometry (GC–MS) is a platform of choice for qualitative and quantitative analysis of OAs in laboratory settings (Bouatra et al, ), because of its advantages including high sensitivity, peak resolution and reproducibility. This technology has been applied to determine changes in global metabolite profiling in urine from patients with prostate (Lima et al, ), bladder (Zhou et al, ) and renal cancers (Monteiro et al, ). Several important observations regarding altered levels of OAs have recently been obtained from GC–MS.…”
Section: Introductionmentioning
confidence: 99%
“…Gas chromatography mass spectrometry (GC–MS) is a platform of choice for qualitative and quantitative analysis of OAs in laboratory settings (Bouatra et al, ), because of its advantages including high sensitivity, peak resolution and reproducibility. This technology has been applied to determine changes in global metabolite profiling in urine from patients with prostate (Lima et al, ), bladder (Zhou et al, ) and renal cancers (Monteiro et al, ). Several important observations regarding altered levels of OAs have recently been obtained from GC–MS.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the level of 5-hydroxyhexanoic acid was significantly increased in patients with BD [40]. Similarly, another two studies based on urinary metabolite analysis reported that 5-hydroxyhexanoic acid was identified as a “good” classifier for post-stroke depression, and levels of 5-hydroxyhexanoic acid were significantly decreased in the bladder cancer group [41, 42]. In an animal study, the concentration of 5-hydroxyhexanoic acid was significantly decreased in Ginseng polysaccharide-treated diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The use of metabolomic analysis in BC has been primarily focused on the distinction between normal-appearing urothelium and BC. Zhou et al found a urinary four-biomarker panel (5-hydroxyvaleric acid, cholesterol, 3-phosphoglyceric acid and glycolic acid) including important metabolic characteristics (e.g., organic acid metabolism, steroid hormone biosynthesis, glycolysis and glyoxylate metabolism) and defined this panel as a combinatorial biomarker for the differentiation between BC patients and healthy controls (AUC = 0.804 with 78.0% sensitivity and 70.3% specificity in the validation set) [ 219 , 220 ]. Besides, Huang and colleagues reported the elevation of component I and decrease of carnitine C9:1 in BC urine samples, compared to healthy controls, as a promising biomarker panel for the identification of BC patients (92.6% sensitivity and 96.9% specificity; AUC = 0.963) [ 221 ].…”
Section: Liquid Biopsy Biomarkers and Their Clinical Applicationsmentioning
confidence: 99%